The Effect of Bilateral Range of Motion (ROM) on Increasing Upper Arm Muscle Strength in Stroke Patients - Yogi Febriana, Niken Nita; Akbar, Roby Rahmadi (MALATA SAINS INDONESIA, 2024)
Introduction: In cases of stroke, there are several clinical manifestations, one of which is muscle weakness or hemiparesis. A rehabilitation program used to improve patient mobility involves exercise activities. Exercise therapy, such as range of motion (ROM) exercises, involves joint movements through their entire range in all appropriate directions. Objectives: This study aims to determine the effect of bilateral ROM on the improvement of upper limb muscle strength in stroke patients. Methods: This study employed a quantitative research design known as a one-group pre-test and post-test design. Twenty-four respondents were selected using purposive sampling technique at Dr. Sitanala Hospital, Tangerang. Data collection involved two instruments: Bilateral ROM Checklist and Muscle Strength Value Guide. Prior to intervention, respondents underwent muscle strength assessment. Following the intervention, on the fifth day, researchers conducted a post-test by re-measuring muscle strength. Data analysis utilized the paired t-test. Statistical analysis using the dependent t-test (Paired simple t-test) revealed that out of 24 respondents, the mean pre-test score was ± 3.38, and the mean post-test score was ± 4.50. Statistical results yielded a p-value of 0.000 (α < 0.05), suggesting a significant effect of Bilateral Range of Motion (ROM) on muscle strength improvement. Results: There is a significant effect of Range of Motion (ROM) on muscle strength improvement in stroke patients. This study demonstrated that it took 5 days to increase muscle strength from a pre-intervention mean of 3.38 to 4.50 post-intervention. Conclusion: Range of Motion can increase muscle strength in stroke patients, it can be used as an adjunct to nonpharmacological therapy.